2014
DOI: 10.1111/gwao.12043
|View full text |Cite
|
Sign up to set email alerts
|

Collective Bargaining and the Gender Pay Gap in the Printing Industry

Abstract: This paper considers the effect of collective bargaining on the gender pay gap in the printing industry. This sector was subject to multi-employer bargaining for around 90 years, until 2010. The article analyses gendered collective bargaining processes through the mechanism of symbolic power, that is, the power of interpretation and definition, and utilizes Walton and McKersie's seminal work on bargaining behaviour to understand the processes that have prevented the closing of the pay gap. It finds that symbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Both companies called on us to play an expert role during the previous or actual bargaining process, in 2007 for the management side in Power.inc for Author A, in 2015 for the union side in Info.inc for Author B. This approach based on participant observation of collective bargaining has allowed access to behind‐the‐scenes negotiations, internal tensions among stakeholders evolving through the bargaining process, archives and intermediary documents, rather than merely to official statements by management or unions (Acker, ; Dawson, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both companies called on us to play an expert role during the previous or actual bargaining process, in 2007 for the management side in Power.inc for Author A, in 2015 for the union side in Info.inc for Author B. This approach based on participant observation of collective bargaining has allowed access to behind‐the‐scenes negotiations, internal tensions among stakeholders evolving through the bargaining process, archives and intermediary documents, rather than merely to official statements by management or unions (Acker, ; Dawson, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the first ethnography of a ‘comparable‐worth’ implementation, Joan Acker () has shown how the technical is always political: management manipulated job evaluation techniques — provided by private consultants — and unions resisted wage redistribution — potentially detrimental to their male members. In the British printing industry, Tricia Dawson has revealed that both trade unionists and management, mostly male, do not discuss the form of the gender pay hierarchy, reflecting the symbolic power that lies in defining the ‘appropriate bargaining issues’ (bonus and extra payments, male advantages linked to skilled jobs) and the tendency for gender issues to fall off the agenda (Dawson, ). In the Finnish centralized and consensual industrial system, a national pay equity strategy was built in the 1990s, influenced by the Canadian experience and feminist scholars, as an ‘interactive social problem‐solving’ about comparable worth (Hieskanen, ).…”
Section: Equality Bargaining and Quantification Of Gender Inequalitiesmentioning
confidence: 99%
“…Understanding of such relationships is filtered through existing beliefs, attitudes and positioning of key actors. If collective bargaining is by nature a conflictual process which seeks to resolve antagonistic views (Barbash ), equality bargaining therefore presents an additional set of potential conflicts (Chappe and Pochic ; Dawson ; Laufer ). Conflicts over proposed actions are not necessarily apparent in the text of an agreement: as noted above, they may become visible where an external actor has intervened to demand revision of an agreement; they also appear in some cases where a formal statement of non‐agreement is appended (Datatech, Gazia), but such statements are not always included.…”
Section: Actions To Promote Gender Equality In Agreements and Plansmentioning
confidence: 99%
“…More recently, the Finnish centralized collective bargaining system has protected male privilege in the labour market through the strong tendency to uphold gendered divisions in the market and in collective bargaining. In collective bargaining, gendered power relations operate so that women's interests tend to become marginalized in the process (Dawson, ).…”
Section: The Undervaluation Of Feminized Care Workmentioning
confidence: 99%
“…In collective bargaining, gendered power relations operate so that women's interests tend to become marginalized in the process (Dawson, 2014).…”
Section: Nurses Trade Unions and Equal Paymentioning
confidence: 99%